Management of noninfectious posterior uveitis with intravitreal drug therapy - Tan HY (Dove Medical Press, 2016)
Hui Yi Tan,1 Aniruddha Agarwal,2 Cecilia S Lee,3 Jay Chhablani,4 Vishali Gupta,5 Manoj Khatri,6 Jayabalan Nirmal,7 Carlos Pavesio,8 Rupesh Agrawal1,7–9 1Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 2Department of Vitreoretina, Stanley M Truhlsen Eye Institute, University of Nebraska Medical Center, Omaha, NE, 3Department of Ophthalmology, University of Washington, Seattle, WA, USA; 4Department of Vitreoretina, L V Prasad Eye Institute, Hyderabad, Telangana, 5Department of Retina and Uvea, Post Graduate Institute of Medical Education and Research, Chandigarh, 6Department of Retina, Rajan Eye Care Hospital, Chennai, Tamil Nadu, India; 7School of Material Science and Engineering, Nanyang Technological University, Singapore; 8Department of Medical Retina, Moorfields Eye Hospital, NHS Foundation Trust, London, UK; 9Department of Ophthalmology, National Healthcare Group Eye Institute, Tan Tock Seng Hospital, Singapore Abstract: Uveitis is an important cause of vision loss worldwide due to its sight-threatening complications, especially cystoid macular edema, as well as choroidal neovascularization, macular ischemia, cataract, and glaucoma. Systemic corticosteroids are the mainstay of therapy for noninfectious posterior uveitis; however, various systemic side effects can occur. Intravitreal medication achieves a therapeutic level in the vitreous while minimizing systemic complications and is thus used as an exciting alternative. Corticosteroids, antivascular endothelial growth factors, immunomodulators such as methotrexate and sirolimus, and nonsteroidal anti-inflammatory drugs are currently available for intravitreal therapy. This article reviews the existing literature for efficacy and safety of these various options for intravitreal drug therapy for the management of noninfectious uveitis (mainly intermediate, posterior, and panuveitis). Keywords: intravitreal therapy, noninfectious uveitis, posterior uveitis, intravitreal steroids, intravitreal methotrexate